Pengaruh Kepemimpinan Kepala Sekolah dan Pemenuhan Standar Sarana Prasarana terhadap Prestasi Siswa - Mardani Mardani; Mohamad Jaenudin; Amie Primarni (Jurnal Dirosah Islamiyah, 2020)
Student achievement is one indicator of graduate quality or student quality as well as school credibility. Often the quality of graduates and student achievement is one of the references or references for prospective new students to register at the school. But what influences student achievement is not solely the internal factors of students who are easy or difficult to get proper education. Other factors also support or hinder student achievement, including Principal Leadership, availability of educational facilities and infrastructure, availability of learning media, teacher competence, parental support, curriculum, and so on. The purpose of this study was to determine the effect of Principal Leadership and the fulfillment of infrastructure standards on student achievement in Al Qudwah Islamic Middle School, Cibinong, Bogor. The research method used in this study is a quantitative method. This research is correlational because the research seeks to investigate the influence of School Principal Leadership, Fulfillment of Infrastructure Facilities, on Student Achievement at Al Qudwah Islamic Middle School, Cibinong, Bogor. Data collection techniques using the study of literature, documentation, observation, and questionnaires. Data analysis techniques using correlation and regression analysis. The results showed that (a) the Principal's Leadership contributed very significantly and influenced rather high and the direction of a positive relationship to student achievement in Al Qudwah Islamic Middle School, Cibinong, Bogor Regency (b) Fulfillment of Infrastructure Standards contributes very significantly and influences high and the direction of the relationship positive towards student achievement at Al Qudwah Islamic Middle School, Cibinong, Bogor Regency. Correlation coefficient Variable Fulfillment of Infrastructure to Student Achievement, and (c) The relationship of Principal Leadership and Fulfillment of Infrastructure Facilities is strong to student achievement in Al Qudwah Islamic Middle School, Cibinong, Bogor Regency. Keyword: Leadership, Infrastructure, Student Achievement